Clinical and radiological predictors of adverse outcomes after unilateral biportal endoscopic surgery for short-segment degenerative lumbar spinal stenosis - Qiang Zhang; Ninghao Liu; Dawei Li; Yingjie Zheng (Frontiers in Surgery, 2026)
Objective Complications of lumbar spine stenosis surgery is not uncommon, and focusing on predicting complications following spinal endoscopic surgery remain limited. Our study aimed to collect clinical and imaging markers to identify risk factors for postoperative complications in spinal endoscopic surgery. Methods Retrospective analysis was conducted on clinical and imaging data from patients undergoing unilateral laminotomy for bilateral decompression (ULBD) surgery to predict postoperative complications. Bone density was assessed using the CT Hounsfield unit measurement method. Univariate and multivariate analyses were performed to identify factors influencing postoperative complications, and clinical outcomes before and after UBE surgery were compared. Finally, the predictive validity of these factors was evaluated using receiver operating characteristic (ROC) curve analysis, providing a reliable assessment of their clinical application value. Results This study included 166 patients who underwent short-level ULBD surgery, of whom 23 experienced postoperative complications. Compared with the non-complication group, patients in the complication group were older (71.35 ± 5.89 vs. 66.42 ± 8.27, P = 0.007) and had a longer duration of symptoms (26.09 ± 16.83 vs. 8.90 ± 3.87, P < 0.001). Multivariate analysis identified symptom duration exceeding one year as the sole independent risk factor for postoperative complications following ULBD surgery, with a prediction accuracy of 95.3%. Functional outcomes after UBE surgery were significantly improved compared with preoperative status in all patients. Conclusion ULBD surgery demonstrates high efficacy in treating short-segment lumbar spinal stenosis. A symptom duration exceeding 15.55 months is an independent risk factor for postoperative complications following ULBD.